"Bidding the project" vs. "bidding the envelope" in public sector infrastructure procurements. (May 2018) - Basso, Leonardo J.; Ross, Thomas W.
Abstract: We study the relative efficiency of two mechanisms actually employed in large-scale public procurements, often for transportation projects such as roads, bridges and rapid transit systems. In the more common "bidding the project" mechanism, the government specifies the size of the project (a quantity) and firms bid prices (the lowest bid winning). In the "bidding the envelope" mechanism the government specifies what it is willing to spend and firms bid quantities (the highest winning). With uncertainty about project costs and benefits, the much less frequently applied "bidding the envelope" mechanism can lead to higher value for money. Its advantage lies in its ability to allow quantity to adjust to high or low costs. Highlights: Public procurement can involve bidding on defined projects or bidding to do the most within an available envelope. Depending on the nature of uncertainty about costs, either bidding approach can dominate in terms of value for money. "bidding the project" controls output but does not allow for project scale to adapt to costs.